PENGARUH DOSIS PUPUK UREA DAN PUPUK HAYATI MIKORIZA TERHADAP PERTUMBUHAN TANAMAN JAGUNG (Zea Mays. L) - Wiyono; Daryanti; Setya Fikrie Afifuddin; Setie Harieni (JURNAL ILMIAH AGRINECA, 2021)
The efficiency of inorganic fertilizers can also be done by using mycorrhizal biofertilizers. Efforts to increase corn growth need to be done by using inorganic fertilizers and biological fertilizers. This study aims to determine the effect of urea and mycorrhizae doses on the growth of maize (Zea mays. L). The research was conducted in Gejugan Village, Andong District, Boyolali Regency, an altitude of 154 m above sea level with grumusol soil type. This study used a completely randomized block design (RAKL) with two treatment factors, namely the first factor urea fertilizer dosage consisting of 4 levels, namely N0 = 0 kg / ha, N1 = 100 kg / ha, N2 = 200 kg / ha, N3 = 300 kg. / ha, and mycorrhizae consists of 3 levels, namely M0 = 0 g / plant, M1 = 5 g / plant, M2 = 10 g / plant. with 3 repetitions. The results of this study indicated that the dose of urea fertilizer affected the growth of maize, while the mycorrhizal dose did not affect the growth of maize except for the length of the plant roots. The effect of urea dose interaction with mycorrhizae only affected the root length growth of maize. The best growth of maize plants after being given a dose of urea as much as 100 kg/da and mycorrhizal biofertilizer 10 g / plant with the longest roots (40.44 cm)